The prescription rule analysis of the new theory on spleen dampness syndrome by academician TONG Xiaolin - Zheng Jinghui; Li Lijuan; Huang Feijian; Chen Xuan; Lei Ye; Zhu Xiangdong; Liu Wenke (KeAi Communications Co., Ltd., 2022)
Objective: To analyze the basic characteristics, drug features, prescription rules, and drug-symptom relationships of patients in the splenic deficiency and impairment stage, by data mining of medical records under the New Theory on Spleen Dampness Syndrome (Pi Dan Xin Lun, 《脾瘅新论》). Methods: Medical records listed in the "New Theory on Spleen Dampness Syndrome - Understanding and Treatment of Metabolic Syndrome from the Perspective of Traditional Chinese Medicine", and which were diagnosed with the spleen dampness syndrome at the splenic deficiency and impairment stage, during January 2004 and December 2016 were selected. These patients' data, including basic information, clinical symptoms, laboratory examination results, traditional Chinese medicine (TCM) and western medicine diagnoses, treatment methods, prescriptions, etc., were collected. The collected data were subsequently compiled into a medical record database using the Epidata 3.1 data management software, followed by the use of Apriori algorithm provided in the SPSS Modeler 14.2 statistical software to investigate the association rules between drug-drug, drug-symptom, and drug-western medicine indices. Results: (i) A total of 51 medical records were included, involving 17 types of syndromes. Among them, the top three with frequency ≥3 included "Phlegm and blood stasis, and thoracic obstruction" "Deficiency-weakness of the spleen Qi, and static blood blocking collaterals", and "Deficiency-weakness of the spleen Qi, and static blood blocking collaterals". Alternatively, of the 14 treatment methods, the top three treatments with frequency of ≥3 included "Activating Yang and eliminating turbidity, and removing phlegm and dredging channel blockage" "Strengthening the spleen and benefiting Qi, and eliminating phlegm to activate the channels", and "Warming Yang and benefiting Qi, and expelling cold to remove obstructions". Among the 15 prescriptions, the top three used with frequency ≥3 included Huangqi Guizhi Wuwu Tang (黄芪桂枝五物汤), Gualou Xiebai Banxia Tang (瓜蒌薤白半夏汤), and Ganjiang Huangqin Huanglian Renshen Tang (干姜黄芩黄连人参汤). Lastly, of the 83 drugs used for a total of 476 times, those with frequency ≥15 included Huanglian (Coptidis Rhizoma), Huangqi (Astragali Radix), Jiudahuang (Wine-processed Rhei Radix et Rhizoma), Jixueteng (Spatholobi Caulis), Shengjiang (Zingiberis Rhizoma Recens), Huangqin (Scutellariae Radix), and Guizhi (Cinnamomi Ramulus). (ii) For the drug-drug associations, under the criteria of support ≥15% and confidence = 100%, 7 s-order association rules, seven third-order rules, and six fourth-order roles were identified. The top-ranking rule of each was "Huangqin (Scutellariae Radix) → Huanglian (Coptidis Rhizoma)" "Ganjiang (Zingiberis Rhizoma) + Huangqin (Scutellariae Radix) → Huanglian (Coptidis Rhizoma)", and "Baishao (Paeoniae Radix Alba) + Guizhi (Cinnamomi Ramulus) + Jixueteng (Spatholobi Caulis) → Huangqin (Scutellariae Radix)", respectively. Alternatively, the drug-symptom associations were analyzed under the criteria of support ≥5% and confidence = 100%, which derived 8 s-order association rules, 31 third-order rules, and 30 fourth-order rules. The top-ranking association rule of each order was "Huangqi (Astragali Radix) → Limb edema" "Guizhi (Cinnamomi Ramulus) + Jixueteng (Spatholobi Caulis) → Limb numbness and pain", and "Guizhi (Cinnamomi Ramulus) + Jixueteng (Spatholobi Caulis) + Huangqi (Astragali Radix) → Limb numbness and pain", respectively. Similarly, the drug-western medicine index associations were investigated under the criteria of support ≥5% and confidence = 100%, and 5 s-order association rules, 16 third-order rules, and 16 fourth-order rules were identified. In this category, the top-ranking association rule of each order was "Qinpi (Fraxini Cortex) → Uric acid" "Huanglian (Coptidis Rhizoma) + Ganjiang (Zingiberis Rhizoma) → Glycated hemoglobin", and "Huanglian (Coptidis Rhizoma) + Ganjiang (Zingiberis Rhizoma) + Huangqin (Scutellariae Radix) → Glycated hemoglobin", respectively. Conclusion: Through association rule mining, this study objectively and quantitatively demonstrated the drug-drug, drug-symptom, and drug-physicochemical index associations of patients with the spleen dampness syndrome at the splenic deficiency and impairment stage treated by Academician TONG Xiaolin. The results indicated that treatment for these patients adopted the "state-target" syndrome differentiation method. The drug combination was characterized by "small prescriptions", targeting both the patient's symptoms and signs (syndrome target) and western medicine indices (treatment target). This study could provide references for future research on the academic thoughts and medical experience of Academician TONG Xiaolin.